2020
DOI: 10.1108/ijhrh-01-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Japanese-style health program in Minowa Town, Matsumoto city and Nagano city, Japan

Abstract: Purpose This study aims to establish a Japanese-style healthcare program customized for Japan and Asia under ISO 9001: 2008 (ISO: International Organization for Standardization) to improve problem areas and to inspect the effectiveness of the program. Furthermore, the authors wanted to create this health program using the ISO widely available in Asian countries and make an international contribution. Design/methodology/approach The authors implemented a 6- to 10-month health program in Minowa Town, Matsumoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 12 publications
(19 reference statements)
0
12
0
2
Order By: Relevance
“…However, there are few improvement items for physical fitness in Thailand, Indonesia, and Japan. If the average number of total steps taken by participants is 7,000 or more, the improvement rate of physical fitness measurement items will significantly increase [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are few improvement items for physical fitness in Thailand, Indonesia, and Japan. If the average number of total steps taken by participants is 7,000 or more, the improvement rate of physical fitness measurement items will significantly increase [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…The Thai and Indonesian groups had significantly fewer total "misses" and errors after the program. Previous go/no-go task studies suggest that a health program could improve brain function [5][6][7][8]. In the first stage of the go/no-go task, the reaction time is short and the number of errors is large.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melakukan olahraga secara teratur, efeknya lebih baik terhadap sistem imun jika dibandingkan dengan olahraga yang hanya dilakukan sekli saja. Olahraga bisa merangsang kinerja antibodi dan sel-sel darah putih bisa bersirkulasi lebih cepat (Fujimori, et al, 2020). Sel darah putih merupakan sel kekebalan tubuh yang melawan berbagai penyakit.Adapun durasi ideal olahraga yaitu cukup 30 menit hingga satu jam adapun durasi diatas satu jam justru akan membuat daya tahan tubuh lemah dan rentan (Kholis, Lusianti, Harmono, Yuliawan, & Rizky, 2020 Lentera Negeri musik atau tarian tradisional dengan durasi yang telah ditentukan.…”
Section: Pendahuluanunclassified
“…Some studies have shown that the aging process can be delayed and physical fitness can be increased by performing routine physical activity. Moreover, good physical fitness can maintain brain function and blood chemistry [2,3]. Physical activity is important in the context of non-communicable disease prevention [4].…”
Section: Introductionmentioning
confidence: 99%